Receiver initiated fast sequential collision resolution in 802.11 WLAN. (2017) - Jibukumar, M.G.; Shajahan, Shahanas; Lakshmi, P. Sethu; Preetha, P.
Future wireless local area networks (WLANs) have potential bit rates of the order of hundreds of Mbps. However, the current IEEE 802.11 medium access control (MAC) protocol does not scale well to high bit rate WLANs. By using collision detection in wireless networks, the time spent on collision can be reduced, thus improving system throughput. In this paper, we propose an enhancement that uses a tone transmitted on a small time slot (called contention slot) which enables receiver initiated collision detection to the transmitters. In this proposed protocol, the receiver detects the collision when multiple data packets are received and it transmits a jamming signal to all the transmitting stations so that they can immediately stop their ongoing transmissions. In addition to collision detection, we propose a sequential collision resolution mechanism where preferential access is given to all the colliding packets to reduce unfairness and to increase system throughput.